Cardiovascular and metabolic risk profile in german patients with moderate and severe psoriasis: A case control study - Warnecke, Christine; Manousaridis, Ioannis; Herr, Raphael M.; Terris, Darcey D.; Goebeler, Matthias; Goerdt, Sergij; Peitsch, Wiebke K. (European Journal of Dermatology, 2011)
Patients with psoriasis have a higher risk of cardiovascular and metabolic comorbidities, attributable to lifestyle factors, but also to shared inflammatory pathways and genetic factors. To investigate the association between moderate and severe psoriasis and metabolic and cardiovascular comorbidities, 100 patients hospitalized at University Medical Centre Mannheim, Germany, for psoriasis treatment were compared to two ageand sex-matched control groups, the first comprising other hospitalized patients (HCG) and the second comprising healthy individuals from an industrial cohort study (ICG). Multivariate logistic regression analysis with stepwise inclusion of cardiovascular risk factors was performed. Patients with psoriasis had significantly increased prevalences of smoking, obesity, diabetes, insulin resistance, pro-atherogenic cholesterol profiles and myocardial infarction and significantly decreased cardioprotective adiponectin. Unexpectedly, regression models controlling for confounding factors predicted significantly decreased OR for elevated total cholesterol in psoriasis cases (vs HCG: OR=0.50, p=0.045; vs ICG: OR=0.26, p=0.006). In contrast, OR for pro-atherogenic cholesterol profiles with LDL/HDL >3 was markedly increased (OR=2.45, p=0.012 or OR=3.02, p=0.020). Moreover, participants with psoriasis had significantly increased OR for elevated CRP as compared to the ICG (5.25, p=0.001). Our findings underscore the importance of cardiovascular and metabolic risk screening for all patients with moderate and severe psoriasis, including young patients.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Adiponectin; Cholesterol; Inflammation; Insulin resistance; Myocardial infarction; Psoriasis